2005
DOI: 10.1002/fuce.200400064
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical and Structural Nature of Proton Exchange Membrane Fuel Cell Properties

Abstract: The chemical and structural (morphological) features of proton exchange membranes are directly tied to their fuel cell relevant transport properties. A large body of research has focused on characterizing the structure or investigating the properties of Nafion® and other proton exchange membranes, but few studies have linked chemical composition to membrane morphology, and resulting transport properties. This paper systematically discusses the key chemical and structural features of proton exchange membranes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
273
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(277 citation statements)
references
References 47 publications
4
273
0
Order By: Relevance
“…Low cost and ready availability are important economical requirements. Furthermore, the membrane should work at an operative temperature around 120 • C for long time [1][2][3]. Although there is much interest in the development of an "ideal" membrane, there is nowadays no material that can completely satisfy the required performances [4].…”
Section: Introductionmentioning
confidence: 99%
“…Low cost and ready availability are important economical requirements. Furthermore, the membrane should work at an operative temperature around 120 • C for long time [1][2][3]. Although there is much interest in the development of an "ideal" membrane, there is nowadays no material that can completely satisfy the required performances [4].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphosphazenes [8,9], polybenzimidazole [10], poly(ether sulfone)s [11,12], and poly(ether ketone)s [13][14][15] have been used to prepare membranes for fuel cell applications. These polymers have received much attention because of their high thermal, oxidative, and chemical stability in fuel cell environments, and their performance close to Nafion's [16].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high performance and durability as well as reduction of the cost, the improvement of a wide range of properties for proton exchange membrane (PEM) is required, such as thermal stability, high ionic conductivity at low humidity, and elongated lifetime. [1][2][3] Perfluorosulfonic acid (PFSA) ionomers such as Nafion © are commonly used due to their high proton conductivity and chemical stability. However, low glass transition temperature, high gas permeability, environmental inadaptability as well as high production cost are issues to overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonic acid groups combined with water molecules are known to form spherically-shaped hydrophilic clusters and organize the phase-separated structure inside a Nafion membrane; the hydrophilic clusters are interconnected by narrow ionic channels to form a proton conductive network in hydrophobic fluorocarbon matrix. 2,4,6,20 By using scanning transmission electron microscopy (STEM), we reported that the SPK multiblock copolymers also have a well-ordered hydrophilic/hydrophobic phase-separated structure and that the sizes of hydrophilic and hydrophobic clusters were larger than those of Nafion. 19 It should be mentioned, however, that those phase-separated morphologies observed under vacuum and dry conditions are not necessarily identical with the proton conduction paths inside the electrolyte membranes, therefore, the proton conductive paths themselves must be investigated under the conditions similar to those of operating fuel cells.…”
Section: Introductionmentioning
confidence: 99%